A processing method for improved plastics

By performing multi-step treatment of barite powder and graphene, functional fillers are prepared and used for processing of improved plastics, the problems of low strength and short service life of existing plastic products are solved, and the strength and service life of the plastic are significantly improved.

CN119775668AInactive Publication Date: 2025-04-08安徽霍山中豪新材料科技有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510062298.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing plastic products have problems of low strength and short service life, which is difficult to meet the needs of complex application environments.

Method used

A modified plastic processing method is adopted to obtain a functional filler by bead grinding of barite powder and graphene, flame-ultrasonic coupling, high temperature and high pressure, and mixing it with other raw materials for injection molding.

Benefits of technology

It significantly improves the filling characteristics of functional fillers and the strength of plastics, extends the service life of plastics, and improves its performance in complex application environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a processing method for improved plastics, which belongs to the field of plastic processing technology and comprises the following steps: (1) bead milling; (2) flame-ultrasonic coupling treatment; (3) high temperature and high pressure treatment; (4) centrifugal treatment; (5) raw material weighing; (6) injection molding. The present application provides a processing method for improved plastics, wherein a functional filler is obtained by sequentially subjecting barite powder and graphene to bead milling, flame-ultrasonic coupling, high temperature and high pressure treatments, etc. The bead milling, flame-ultrasonic coupling, high temperature and high pressure treatments can significantly improve the filling characteristics of the functional filler, and the functional filler obtained by the method of the present application can significantly improve the strength of the plastic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plastic processing, in particular to a processing method of improved plastic. Background Art

[0002] Plastic is a material with a certain shape, which is made of high-molecular compounds such as resin as the basic component, and is mixed with other ingredients and then heated and pressurized. At room temperature, the shape of plastic will not change. It is usually composed of synthetic resin as the main component and may contain auxiliary materials such as plasticizers, stabilizers, lubricants and colorants.

[0003] Plastic products are widely used in various fields due to their advantages such as lightness, durability, low cost, easy processing, moisture resistance and corrosion resistance. However, most plastic products on the market today have the problems of low strength and short service life. Summary of the invention

[0004] The object of the present invention is to provide a method for processing improved plastics to solve the deficiencies in the prior art.

[0005] The technical solution adopted by the present invention is as follows: A method for processing improved plastics comprises the following steps: (1) Bead milling: Place barite powder and graphene in a bead mill at a weight ratio of 1:20-30 for grinding, and obtain a mixed powder for later use; (2) Flame-ultrasonic coupling treatment: The mixed powder obtained in step (1) is placed on the outer flame of the flame for flame treatment, and ultrasonic treatment is performed during the flame treatment. After completion, the mixed powder is taken out for use; (3) High temperature and high pressure treatment: The mixed powder after the flame-ultrasonic coupling treatment in step (2) and the treatment liquid are placed in a reaction kettle at a weight volume ratio of 1 mg: 10-20 mL, and then the temperature in the reaction kettle is increased to 200-230° C., and the pressure in the reaction kettle is increased to 3-5 MPa. After high temperature and high pressure treatment for 10-20 minutes, the pressure is quickly reduced to normal pressure, and the mixture is taken out for use; (4) Centrifugal treatment: The mixture obtained in step (3) is placed in a high-speed centrifuge for high-speed centrifugation. After completion, the supernatant is discarded, the precipitate is washed 5 to 9 times by centrifugation with pure water, and then dried to obtain the functional filler for use; (5) Weighing of raw materials: Weigh corresponding weight portions of 12-18 parts of the functional filler obtained in step (4), 80-90 parts of polypropylene, 30-40 parts of rosin, 2-3 parts of diisodecyl phthalate, 5-7 parts of potassium stearate, 3-4 parts of oleic acid, 1-2 parts of carboxylic acid, and 100-140 parts of deionized water for later use; (6) Injection molding: All the raw materials weighed in step (5) are put into a mixer for mixing, and then put into a twin-screw extruder for extrusion molding.

[0006] Furthermore, during the grinding process in step (1), the rotation speed of the grinder is controlled to be 2000-4000 rpm, and the grinding time is 30-40 min.

[0007] By adopting the above technical solution, barite powder and graphene are placed in a bead mill for grinding in a suitable proportion. During the grinding process, the barite powder and graphene fully absorb the kinetic energy generated by the grinding, weakening the interface effect between the two components and preventing the occurrence of agglomeration.

[0008] Furthermore, during the flame treatment in step (2), the horizontal distance between the mixed powder and the outer flame is controlled to be 1-2 cm, and the flame treatment time is 10-15 min.

[0009] Furthermore, during the ultrasonic treatment in step (2), the frequency of the ultrasonic wave is controlled to be 80-90 kHz.

[0010] By adopting the above technical scheme, the gas flame contains free radicals such as O, NO, OH and NH in an excited state, and then the surface is oxidized according to the free radical mechanism, and some polar oxygen-containing groups are introduced to cause chain breaking reaction, thereby improving the surface adhesion and wettability. Combined with the acoustic streaming effect and cavitation effect of ultrasound, the surface of the mixed powder is refined, and the two are closely combined to form a homogeneous, refined and stable composite powder.

[0011] Furthermore, the components and corresponding weight percentages in the treatment liquid described in step (3) are: silane coupling agent 5-7%, soybean lecithin 10-12%, sodium dodecylbenzene sulfonate 8-10%, propylene glycol 1-2%, carboxymethyl cellulose 3-5%, and the balance is deionized water.

[0012] Furthermore, during the high-speed centrifugation treatment in step (4), the speed of the centrifuge is controlled to be 7000-9000 rpm, and the time of the high-speed centrifugation treatment is 10-16 min.

[0013] By adopting the above technical scheme, the mixed powder after flame-ultrasonic coupling treatment and the treatment liquid are placed in a reactor in a suitable proportion. When the temperature rises to a certain level, since the raw material contains a certain amount of water, when the pressure is released quickly, the high-temperature and high-pressure water inside the raw material is released instantly, generating a huge flash explosion force, thereby destroying the physical structure of the mixed powder, achieving dissociation, structural destruction and composition change, and then high-speed centrifugation is performed to obtain a functional filler with a good filling effect.

[0014] The present invention has the following beneficial effects: The present application provides a method for processing improved plastics, wherein a functional filler is obtained by sequentially subjecting barite powder and graphene to bead milling, flame-ultrasonic coupling, high temperature and high pressure treatments, and the like. By comparing Examples 4 to 6 with Example 2, it can be concluded that bead milling, flame-ultrasonic coupling, high temperature and high pressure treatments can significantly improve the filling characteristics of the functional filler. By comparing Examples 7 to 8 and the control group with Example 2, it can be concluded that the functional filler obtained by the method of the present application can significantly improve the strength of the plastic. DETAILED DESCRIPTION

[0015] The following will be described clearly and completely in conjunction with the technical solutions of the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0016] A method for processing improved plastics comprises the following steps: (1) Bead milling: The barite powder and graphene are placed in a bead mill at a weight ratio of 1:20 for grinding, and the mixed powder is ready for use; (2) Flame-ultrasonic coupling treatment: The mixed powder obtained in step (1) is placed on the outer flame of the flame for flame treatment, and ultrasonic treatment is performed during the flame treatment. After completion, the mixed powder is taken out for use; (3) High temperature and high pressure treatment: The mixed powder after the flame-ultrasonic coupling treatment in step (2) and the treatment liquid are placed in a reactor at a weight volume ratio of 1 mg:10 mL, and then the temperature in the reactor is increased to 200° C., the pressure in the reactor is increased to 3 MPa, and after high temperature and high pressure treatment for 10 minutes, the pressure is quickly reduced to normal pressure, and the mixture is taken out for use; (4) Centrifugal treatment: The mixture obtained in step (3) is placed in a high-speed centrifuge for high-speed centrifugation. After completion, the supernatant is discarded, the precipitate is washed 5 times by centrifugation with pure water, and then dried to obtain the functional filler for use; (5) Weighing of raw materials: Weigh corresponding weight portions of 12 parts of the functional filler obtained in step (4), 80 parts of polypropylene, 30 parts of rosin, 2 parts of diisodecyl phthalate, 5 parts of potassium stearate, 3 parts of oleic acid, 1 part of carboxylic acid, and 100 parts of deionized water for later use; (6) Injection molding: All the raw materials weighed in step (5) are put into a mixer for mixing, and then put into a twin-screw extruder for extrusion molding.

[0017] During the grinding process described in step (1), the rotation speed of the grinder is controlled to be 2000 rpm and the grinding time is 30 min.

[0018] During the flame treatment in step (2), the horizontal distance between the mixed powder and the outer flame of the flame is controlled to be 1 cm, and the flame treatment time is 10 minutes.

[0019] During the ultrasonic treatment in step (2), the frequency of the ultrasonic wave is controlled to be 80 kHz.

[0020] The components and corresponding weight percentages in the treatment liquid described in step (3) are: 5% silane coupling agent, 10% soybean lecithin, 8% sodium dodecylbenzene sulfonate, 1% propylene glycol, 3% carboxymethyl cellulose, and the balance is deionized water.

[0021] During the high-speed centrifugation treatment in step (4), the speed of the centrifuge is controlled to be 7000 rpm, and the time of the high-speed centrifugation treatment is 10 minutes. Example 2

[0022] A method for processing improved plastics comprises the following steps: (1) Bead milling: Place barite powder and graphene in a bead mill at a weight ratio of 1:25 for grinding, and obtain a mixed powder for later use; (2) Flame-ultrasonic coupling treatment: The mixed powder obtained in step (1) is placed on the outer flame of the flame for flame treatment, and ultrasonic treatment is performed during the flame treatment. After completion, the mixed powder is taken out for use; (3) High temperature and high pressure treatment: The mixed powder after the flame-ultrasonic coupling treatment in step (2) and the treatment liquid are placed in a reactor at a weight volume ratio of 1 mg:15 mL, and then the temperature in the reactor is increased to 215° C., and the pressure in the reactor is increased to 4 MPa. After high temperature and high pressure treatment for 15 minutes, the pressure is quickly reduced to normal pressure, and the mixture is taken out for use; (4) Centrifugal treatment: The mixture obtained in step (3) is placed in a high-speed centrifuge for high-speed centrifugation. After completion, the supernatant is discarded, the precipitate is washed 7 times by centrifugation with pure water, and then dried to obtain the functional filler for use; (5) Weighing of raw materials: Weigh corresponding weight portions of 15 parts of the functional filler obtained in step (4), 85 parts of polypropylene, 35 parts of rosin, 2.5 parts of diisodecyl phthalate, 6 parts of potassium stearate, 3.5 parts of oleic acid, 1.5 parts of carboxylic acid, and 120 parts of deionized water for later use; (6) Injection molding: All the raw materials weighed in step (5) are put into a mixer for mixing, and then put into a twin-screw extruder for extrusion molding.

[0023] During the grinding process described in step (1), the rotation speed of the grinder is controlled to be 3000 rpm and the grinding time is 35 min.

[0024] During the flame treatment in step (2), the horizontal distance between the mixed powder and the outer flame of the flame is controlled to be 1.5 cm, and the flame treatment time is 12.5 minutes.

[0025] During the ultrasonic treatment in step (2), the frequency of the ultrasonic wave is controlled to be 85 kHz.

[0026] The components and corresponding weight percentages in the treatment solution described in step (3) are: 6% silane coupling agent, 11% soybean lecithin, 9% sodium dodecylbenzene sulfonate, 1.5% propylene glycol, 4% carboxymethyl cellulose, and the balance is deionized water.

[0027] During the high-speed centrifugation treatment in step (4), the speed of the centrifuge is controlled to be 8000 rpm, and the time of the high-speed centrifugation treatment is 13 minutes. Example 3

[0028] A method for processing improved plastics comprises the following steps: (1) Bead milling: Place barite powder and graphene in a bead mill at a weight ratio of 1:30 for grinding, and obtain a mixed powder for later use; (2) Flame-ultrasonic coupling treatment: The mixed powder obtained in step (1) is placed on the outer flame of the flame for flame treatment, and ultrasonic treatment is performed during the flame treatment. After completion, the mixed powder is taken out for use; (3) High temperature and high pressure treatment: The mixed powder after the flame-ultrasonic coupling treatment in step (2) and the treatment liquid are placed in a reactor at a weight volume ratio of 1 mg:20 mL, and then the temperature in the reactor is increased to 230° C., the pressure in the reactor is increased to 5 MPa, and after high temperature and high pressure treatment for 20 minutes, the pressure is quickly reduced to normal pressure, and the mixture is taken out for use; (4) Centrifugal treatment: The mixture obtained in step (3) is placed in a high-speed centrifuge for high-speed centrifugation. After completion, the supernatant is discarded, the precipitate is washed 9 times by centrifugation with pure water, and then dried to obtain the functional filler for use; (5) Weighing of raw materials: Weigh corresponding weight portions of 18 parts of the functional filler obtained in step (4), 90 parts of polypropylene, 40 parts of rosin, 3 parts of diisodecyl phthalate, 7 parts of potassium stearate, 4 parts of oleic acid, 2 parts of carboxylic acid, and 140 parts of deionized water for later use; (6) Injection molding: All the raw materials weighed in step (5) are put into a mixer for mixing, and then put into a twin-screw extruder for extrusion molding.

[0029] During the grinding process described in step (1), the rotation speed of the grinder is controlled to be 4000 rpm and the grinding time is 40 min.

[0030] During the flame treatment in step (2), the horizontal distance between the mixed powder and the outer flame of the flame is controlled to be 2 cm, and the flame treatment time is 15 minutes.

[0031] During the ultrasonic treatment in step (2), the frequency of the ultrasonic wave is controlled to be 90 kHz.

[0032] The components and corresponding weight percentages in the treatment liquid described in step (3) are: silane coupling agent 7%, soybean lecithin 12%, sodium dodecylbenzene sulfonate 10%, propylene glycol 2%, carboxymethyl cellulose 5%, and the balance is deionized water.

[0033] During the high-speed centrifugation treatment in step (4), the speed of the centrifuge is controlled to be 9000 rpm, and the time of the high-speed centrifugation treatment is 16 minutes.

[0034] Comparative Example 1 Compared with Example 2, in this comparative example 1, the flame treatment process is omitted in step (2) the flame-ultrasonic coupling treatment, and other method steps are the same.

[0035] Comparative Example 2 Compared with Example 2, this comparative example 2 omits the ultrasonic treatment process in step (2) flame-ultrasonic coupling treatment, and other method steps are the same.

[0036] Comparative Example 3 Compared with Example 2, this comparative example 3 omits the entire process of step (2) flame-ultrasonic coupling treatment, and other method steps are the same.

[0037] Comparative Example 4 Compared with Example 2, in this comparative example 4, the functional filler is replaced with an equal mass portion of barite powder in the raw material weighing step (5). Other method steps are the same.

[0038] Comparative Example 5 Compared with Example 2, in this comparative example 5, the functional filler is replaced with an equal mass portion of graphene powder in the raw material weighing step (5), and other method steps are the same.

[0039] Comparative Example 6 Compared with Example 2, in this comparative example 6, the functional filler is replaced with an equal mass portion of polypropylene in the raw material weighing step (5). Other method steps are the same.

[0040] Control group Application number: CN201610710337.0 discloses a high-strength plastic and a preparation method thereof.

[0041] In order to compare the effects of the present application, plastics were prepared using the methods of the above-mentioned Example 2, Comparative Examples 1 to 6 and the control group, and then the tensile strength and elongation at break were tested according to GB / T 1040.1-2006 "Tensile Properties of Plastics"; the cantilever beam impact strength was tested according to GB / T 1843-2008 "Cantilever Beam Impact Strength of Plastics", and the test temperature was room temperature; the bending strength was tested according to GB / T 9341-2008 "Bending Properties of Plastics", and the experimental speed was 2 mm / min; the specific test comparison data are shown in Table 1 below: Table 1 Tensile elastic modulus (MPa) Tensile strength (MPa) Flexural modulus (MPa) Bending strength (MPa) Izod impact strength (kJ / m2) Example 2 1325.53 45.63 1106.85 39.25 71.36 Comparative Example 1 1235.55 42.31 1102.25 34.52 68.96 Comparative Example 2 1302.65 39.52 1025.52 38.12 62.36 Comparative Example 3 968.25 28.36 831.25 31.36 49.85 Comparative Example 4 896.35 35.21 769.34 29.93 45.36 Comparative Example 5 589.36 19.98 802.36 28.88 51.35 Comparative Example 6 412.68 13.85 582.03 18.26 29.98 Control group 981.36 48.23 739.97 21.25 32.85 As can be seen from Table 1 above, the present application provides a method for processing improved plastics, by sequentially subjecting barite powder and graphene to bead milling, flame-ultrasonic coupling, high temperature and high pressure to obtain a functional filler, and by comparing Examples 4 to 6 with Example 2, it can be concluded that bead milling, flame-ultrasonic coupling, high temperature and high pressure and other treatments can significantly improve the filling characteristics of the functional filler, and by comparing Examples 7 to 8 with Example 2, it can be concluded that the functional filler obtained by the method of the present application can significantly improve the strength of the plastic, and by comparing the control group with Example 2, it can be concluded that the tensile strength, impact strength and flexural strength of the plastic prepared by the method of the present application are improved.

[0042] The above description is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.

Claims

1. A method for processing improved plastics, characterized in that: The steps include: (1) Bead milling: Place barite powder and graphene in a bead mill at a weight ratio of 1:20-30 for grinding, and obtain a mixed powder for later use; (2) Flame-ultrasonic coupling treatment: The mixed powder obtained in step (1) is placed on the outer flame of the flame for flame treatment, and ultrasonic treatment is performed during the flame treatment. After completion, the mixed powder is taken out for use; (3) High temperature and high pressure treatment: The mixed powder after the flame-ultrasonic coupling treatment in step (2) and the treatment liquid are placed in a reaction kettle at a weight volume ratio of 1 mg: 10-20 mL, and then the temperature in the reaction kettle is increased to 200-230° C., and the pressure in the reaction kettle is increased to 3-5 MPa. After high temperature and high pressure treatment for 10-20 minutes, the pressure is quickly reduced to normal pressure, and the mixture is taken out for use; (4) Centrifugal treatment: The mixture obtained in step (3) is placed in a high-speed centrifuge for high-speed centrifugation. After completion, the supernatant is discarded, the precipitate is washed 5 to 9 times by centrifugation with pure water, and then dried to obtain the functional filler for use; (5) Weighing of raw materials: Weigh corresponding weight portions of 12-18 parts of the functional filler obtained in step (4), 80-90 parts of polypropylene, 30-40 parts of rosin, 2-3 parts of diisodecyl phthalate, 5-7 parts of potassium stearate, 3-4 parts of oleic acid, 1-2 parts of carboxylic acid, and 100-140 parts of deionized water for later use; (6) Injection molding: All the raw materials weighed in step (5) are put into a mixer for mixing, and then put into a twin-screw extruder for extrusion molding.

2. A method for processing improved plastic according to claim 1, characterized in that: During the grinding process described in step (1), the rotation speed of the grinder is controlled to be 2000-4000 rpm, and the grinding time is 30-40 min.

3. A method for processing improved plastic according to claim 1, characterized in that: During the flame treatment in step (2), the horizontal distance between the mixed powder and the outer flame of the flame is controlled to be 1-2 cm, and the flame treatment time is 10-15 min.

4. A method for processing improved plastic according to claim 1, characterized in that: During the ultrasonic treatment in step (2), the frequency of the ultrasonic wave is controlled to be 80-90 kHz.

5. A method for processing improved plastic according to claim 1, characterized in that: The components and corresponding weight percentages in the treatment solution described in step (3) are: 5-7% silane coupling agent, 10-12% soybean lecithin, 8-10% sodium dodecylbenzene sulfonate, 1-2% propylene glycol, 3-5% carboxymethyl cellulose, and the balance is deionized water.

6. A method for processing improved plastic according to claim 1, characterized in that: During the high-speed centrifugation treatment in step (4), the speed of the centrifuge is controlled to be 7000-9000 rpm, and the time of the high-speed centrifugation treatment is 10-16 min.

Citation Information

Patent Citations

  • High-strength plastic and preparation method thereof

    CN107778607A